An explosion-proof thermal insulation material for a battery based on a three-dimensional fiber preform, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611064905.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-17
AI Technical Summary
中国专利CN111825423A和CN115449194A通过在气凝胶中加入红外遮光剂和短纤维来改善性能,但均采用所有原料直接混合的方式,未能形成有效的三维网络结构,材料性能仍有不足
1、本发明提供了一种基于三维纤维预制体的电池用防爆隔热材料,以三维耐高温纤维网络作为力学支撑骨架,在纤维表面原位构筑成分、结构与功能逐层渐变的梯度界面层,并填充多尺度隔热功能填料,这是一种全新的材料体系,实现了轻量化、低导热、耐高温、可压缩、抗冲击的多功能一体化热防护。
Smart Images

Figure CN122576527B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal protection technology, and relates to an explosion-proof and heat-insulating material for batteries based on a three-dimensional fiber preform, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy vehicles and energy storage technologies, the energy density of lithium batteries is constantly increasing. However, thermal runaway has become a key bottleneck restricting the safe development of the industry. The internal chemical reactions of power lithium batteries are complex. Under abnormal conditions such as overcharging, over-discharging, short circuits, and mechanical punctures, the cells are highly susceptible to thermal runaway, generating a large amount of heat, with instantaneous temperatures reaching 800-1200℃. Once thermal runaway occurs, it rapidly spreads to adjacent cells, causing a sharp rise in the temperature of the entire battery pack, potentially leading to fires or even explosions, posing a significant threat to life and property.
[0003] In terms of safety protection, the main heat insulation materials currently used in the market include fire-retardant coatings, mica sheets, aerogel felt, and fire-retardant foam. However, these materials generally suffer from drawbacks such as limited functionality, high density, large space occupation, and limited overall protective effect. For example, fire-retardant coatings are mainly used for flame retardancy but lack compressibility and have poor heat insulation; mica sheets, while resistant to thermal shock, are high-density rigid materials, heavy, have poor heat insulation, and are prone to cracking under localized impact; aerogel felt, although with low thermal conductivity, has low strength, is prone to powdering, and is generally not heat-resistant (long-term operating temperature ≤650℃); fire-retardant foam, while able to absorb the expansion stress of the battery cell, is mostly an organic material, flammable, and has limited heat insulation effect. In practical applications, to achieve comprehensive protection, it is often necessary to combine multiple materials, resulting in a large overall volume and weight, which seriously affects the vehicle's energy density and driving range.
[0004] In terms of performance balance, existing materials struggle to achieve a balance between thermal barrier properties, impact resistance, and compressibility. For example, some materials offer good thermal insulation but poor impact resistance, failing to effectively withstand the impact of thermal runaway; others, while possessing some compressibility, have high thermal conductivity, limiting their insulation effectiveness. The market urgently needs a new generation of lightweight, low-thermal-conductivity, high-temperature-resistant, compressible, and impact-resistant multifunctional and compatible thermal insulation and protection materials. In recent years, to address these issues, researchers have begun exploring thermal insulation materials based on aerogel and fiber composites. Chinese patents CN111825423A and CN115449194A improve performance by adding infrared blocking agents and short fibers to aerogels, but both employ direct mixing of all raw materials, failing to form an effective three-dimensional network structure, resulting in insufficient material performance.
[0005] In summary, existing technologies still cannot resolve the fundamental contradiction between "high compressibility" and "low thermal conductivity / high temperature resistance." Therefore, there is an urgent need to develop a novel explosion-proof and heat-insulating material that can achieve integrated construction of the fiber skeleton and functional layers, strong interfacial bonding, and excellent overall performance. Summary of the Invention
[0006] To address the aforementioned problems in the prior art, the present invention aims to provide a battery explosion-proof and heat-insulating material based on a three-dimensional fiber preform, its preparation method, and its application, thereby overcoming the shortcomings of the prior art.
[0007] The present invention employs the following technical solutions to achieve its objective: One aspect of the present invention provides an explosion-proof and heat-insulating material for batteries based on a three-dimensional fiber preform, comprising: A three-dimensional fiber preform, a gradient interface layer formed in situ on the fiber surface of the three-dimensional fiber preform, and a thermal insulation filler dispersed in the fiber network of the three-dimensional fiber preform; The gradient interface layer comprises, from the inside out: an interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nano-ceramic functional layer; The interface activation layer is formed by reacting an active substance with reactive functional groups carried by a supercritical fluid on the fiber surface; the organic-inorganic hybrid transition layer is formed by depositing and / or reacting a first functional precursor carried by a supercritical fluid on the surface of the interface activation layer, wherein the first functional precursor includes organic components and nano-inorganic powders; the inorganic nano-ceramic functional layer is formed by depositing and reacting a second functional precursor carried by a supercritical fluid on the surface of the organic-inorganic hybrid transition layer, wherein the second functional precursor forms an inorganic metal oxide ceramic material after reaction; The organic component is one or more of the following: silane coupling agent, melamine, and polysaccharide; The nano-inorganic powder is one or more of nano-zirconium silicate, nano-zirconium oxide, nano-alumina, nano-titanium dioxide, and nano-silica, and its D50 particle size is 1~200nm. The heat-insulating filler includes aerogel heat-insulating powder, infrared radiation materials, and inorganic toughening materials.
[0008] The three-dimensional network structure of the three-dimensional fiber preform provides space for subsequent functional filler filling and also serves as a mechanical support framework for the material. Preferably, the three-dimensional fiber preform is prepared from high-temperature resistant fibers, which are selected from one or more of the following: high-silica fibers with SiO2 content ≥96%, alumina fibers, zirconium oxide fibers, silicon carbide fibers, mullite fibers, aluminosilicate fibers, potassium hexatitanate fibers, silicon nitride fibers, hexagonal boron nitride fibers, carbon fibers, basalt fibers, and boron fibers.
[0009] More preferably, the bulk density of the three-dimensional fiber preform is 0.10~0.50 g / cm³. 3 The thickness is 1.0~10.0 mm. More preferably, the bulk density of the three-dimensional fiber preform is 0.15~0.35 g / cm³. 3 The thickness is 2.0~5.0mm.
[0010] The gradient interface layer comprises, from the inside out, an interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nanoceramic functional layer. The order from the inside out refers to the order from the fiber surface outwards. All gradient interface layers are constructed using supercritical fluid as a carrier; preferably, the supercritical fluid is supercritical CO2 or supercritical nitrogen.
[0011] The interface activation layer is used to introduce reactive functional groups on the fiber surface, which is beneficial for constructing a high-density, uniformly distributed reactive active sites on the fiber surface. This allows the subsequently deposited organic-inorganic hybrid transition layer and inorganic metal oxide ceramic material to be firmly bonded to the fiber matrix through covalent bonding. The active substance with reactive functional groups is an active compound containing one or more reactive functional groups, including -NH2, -OH, -SH, and -epoxy groups. Preferably, the active substance with reactive functional groups is a silane coupling agent. The silane coupling agent is one or more of aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, and methacrylate-type silane coupling agents, such as KH-540, KH-550, KH-560, KH-570, KH-580, KH-792, KH-562, KH-602, KH-902, and KH-573.
[0012] Preferably, the thickness of the interface activation layer is 1~5 nm.
[0013] The organic-inorganic hybrid transition layer achieves a gradual change in composition and structure from the fiber matrix to the outer inorganic layer, eliminating interfacial stress. Its preparation raw materials include organic components and nano-inorganic powders. Preferably, the organic component is one or more of silane coupling agents, melamine, and polysaccharides; the nano-inorganic powder is one or more of nano-zirconium silicate, nano-zirconium oxide, nano-alumina, nano-titanium dioxide, and nano-silica, with a D50 particle size of 1~200 nm, more preferably 10~100 nm.
[0014] Preferably, the mass ratio of organic components to nano-inorganic powder is 1:2 to 1:10.
[0015] Preferably, the thickness of the organic-inorganic hybrid transition layer is 20~100 nm.
[0016] The inorganic nanoceramic functional layer is used to construct a dense, high-temperature resistant protective barrier on the outermost layer of the fiber, endowing the fiber with excellent high-temperature resistance, oxidation resistance, and thermal shock resistance. The inorganic nanoceramic functional layer is prepared by depositing and reacting a second functional precursor on the surface of an organic-inorganic hybrid transition layer under supercritical fluid conditions. The second functional precursor, after reaction, forms an inorganic metal oxide ceramic material. After the second functional precursor is deposited on the surface of the organic-inorganic hybrid transition layer, it undergoes an in-situ hydrolysis-condensation reaction at 45–70°C (usually with the aid of trace amounts of moisture in the system). The newly formed inorganic ceramic network forms strong chemical bonds with the residual hydroxyl or organic groups in the lower layer; therefore, the bonding force between the inorganic metal oxide ceramic material and the fiber is very strong.
[0017] Preferably, the inorganic metal oxide ceramic material is one or more selected from ZrO2, Al2O3, and TiO2. The second functional precursor is a precursor substance for forming the inorganic metal oxide ceramic material, which is a metal alkoxide selected from one or more selected from zirconium n-propoxide, zirconium n-butoxide, aluminum isopropoxide, aluminum sec-butoxide, tetrabutyl titanate, tetraisopropyl titanate, and titanium isopropoxide.
[0018] Preferably, the thickness of the inorganic nanoceramic functional layer is 30~150nm.
[0019] Preferably, the thermal insulation filler comprises aerogel thermal insulation powder, infrared radiation material, and inorganic toughening material. The combination of aerogel thermal insulation powder, infrared radiation material, and inorganic toughening material can achieve synergistic performance across multiple scales and a wide temperature range, comprehensively considering both the thermal insulation performance and mechanical stability of the material.
[0020] Preferably, the aerogel insulating powder is selected from one or more of silica aerogel, alumina aerogel, titanium dioxide aerogel, zirconium dioxide aerogel, and titanium dioxide-silica composite aerogel, and its D50 particle size is 1~200 nm, more preferably 10~100 nm. Preferably, the mass of the aerogel insulating powder accounts for 40~70 wt% of the total mass of the insulating functional filler.
[0021] Preferably, the infrared radiation material is selected from one or more of silicon carbide, zirconium oxide, heat-reflective titanium dioxide, potassium hexatitanate whiskers, manganese dioxide, cobalt tetroxide, graphene, carbon nanotubes, titanium carbide, and aluminum nitride, and its D50 particle size is 2~50μm, preferably 5~20μm. Preferably, the mass of the infrared radiation material accounts for 15~35wt% of the total mass of the heat-insulating functional filler.
[0022] Preferably, the inorganic toughening material is an inorganic whisker, selected from one or more of potassium hexatite whiskers, silicon carbide whiskers, aluminum borate whiskers, zinc oxide whiskers, magnesium oxide whiskers, mullite whiskers, alumina whiskers, silicon nitride whiskers, calcium sulfate whiskers, calcium carbonate whiskers, and calcium magnesium silicate whiskers. Preferably, the aspect ratio of the inorganic whisker is 10-30, and the diameter is 0.1-5 μm. Preferably, the mass of the inorganic toughening material accounts for 5-20 wt% of the total mass of the thermal insulation functional filler.
[0023] A second aspect of the present invention provides a method for preparing an explosion-proof and heat-insulating material for batteries based on a three-dimensional fiber preform, comprising the following steps: (1) Preparation of three-dimensional fiber preforms; (2) The three-dimensional fiber preform is placed in a supercritical reactor, and supercritical fluid containing an active substance with reactive functional groups, supercritical fluid containing a first functional precursor, and supercritical fluid containing a second functional precursor are sequentially introduced to construct an interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nano-ceramic functional layer on the fiber surface inside the preform to obtain a gradient modified preform. (3) A vacuum-pressure cycling process is used to fill the network pores of the gradient modified preform with a dispersion slurry containing heat-insulating filler. (4) The preform after filling is dried and then molded using a gradient molding process to obtain explosion-proof heat insulation material.
[0024] Preferably, the preparation process of the three-dimensional fiber preform includes: sequentially performing the following on the high-temperature resistant fibers: opening treatment, fiber web formation, multi-layer lamination and reinforcement treatment, or opening treatment and fiber weaving. Finally, the product is cut and dried.
[0025] Optionally, the opening process includes the following steps: feeding the high-temperature resistant fiber raw material into an opening machine with a double-pinning roller structure for opening treatment. The first pinning roller rotates at 600~1000 rpm, and the second pinning roller rotates at 800~1200 rpm. The pinning roller needle cloth is a self-locking metal needle cloth with a needle height of 3~5 mm. The opening treatment time is 2~5 minutes. During the opening process, the fibers are torn and separated under the action of the high-speed rotating pinning rollers, causing the tightly wrapped fiber bundles to gradually disperse into a fluffy single fiber state. At the same time, the opening machine is equipped with a dust collection device to remove dust and impurities from the fibers in a timely manner. The opened fibers are fluffy, with a bulk density reduced to 1 / 5~1 / 10 of the original fibers. There is no longer obvious agglomeration between the fibers, creating favorable conditions for the subsequent web forming process. The breaking strength retention rate of the opened fibers is ≥90%, avoiding fiber damage caused by excessive opening.
[0026] Optionally, the fiber web forming process includes the following steps: preparing a fiber web from the opened fibers using an air-jet web forming machine or a carding web forming machine. The air-jet web forming process includes: using an air-jet web forming machine with an airflow rate controlled at 1500~3000 m³ / h. 3 The speed of the mesh belt is controlled at 1~5 m / min. Fibers are blown onto the forming mesh belt under the action of high-speed airflow. The areal density of the fiber web can be precisely adjusted by controlling the airflow and the mesh belt speed. Airflow forming is suitable for processing short fibers with a length of 6~15mm. The fibers are randomly distributed in three dimensions in the airflow, exhibiting good isotropy. During the forming process, a suction device is installed below the forming mesh belt to remove excess airflow, while simultaneously making the fibers adhere more tightly to the mesh belt. The areal density of the formed fiber web is 30~100 g / m², and the thickness uniformity deviation is ≤5%. The carding forming process includes: using a roller carding machine, with the main cylinder speed at 400~800 rpm, the work roller speed at 80~150 rpm, and the stripping roller speed at 200~400 rpm. The fibers are repeatedly carded and transferred between the cylinder and the work roller to form a uniform fiber web. Carding forming is suitable for processing fibers with a length of 15~30mm. The fibers exhibit a certain orientation in the web, which can be adjusted in subsequent processes. The density of the formed fiber web is 40~120g / m², and the fiber orientation can be controlled by adjusting the speed ratio of the working roller and the stripping roller.
[0027] Optionally, the multilayer lamination includes the following steps: laminating the prepared fiber web in multiple layers according to the designed thickness and areal density. The number of layers is calculated based on the target thickness of the preform, typically 6 to 20 layers. A cross-laying method can be used during lamination, where the laying directions of adjacent fiber web layers alternate between 0° and 90° (the overall layup sequence is 0° / 90° / 0° / 90° / …) to enhance the isotropy of the preform.
[0028] Alternatively, the reinforcement methods may include one or more of needle reinforcement, layered suturing, etc.
[0029] Needle Punching Reinforcement: After lamination, the fiber web is fed into a needle punching machine for needle punching reinforcement. The needle punching machine adopts a double-needle plate structure, with a needle punching frequency of 200~500 needle punches / min, a needle punching depth of 6~12mm, and a needle punching density of 80~200 needle punches / cm². 2 During the needle-punching process, the needle carries fiber bundles through the fiber network layers, forming fiber clusters in the thickness direction, mechanically locking the various fiber network layers together. By controlling the needle-punching density and depth, the volume density and thickness of the precast can be precisely adjusted. The needle-reinforced precast exhibits good structural stability, with a thickness-direction peel strength ≥0.5 N / cm.
[0030] Layered sewing: After layering the fiber cloth in the design direction, sew it together with a sewing machine. The sewing thread is the same material as the fiber cloth, and the sewing interval is 5~15mm to form a layered sewing prefabricated body.
[0031] Weaving: The fibers are directly woven into three-dimensional four-dimensional, five-dimensional or multi-directional woven preforms with a weaving angle of 15~45° and a fiber volume fraction of 20~40%.
[0032] Optionally, cutting and drying: The reinforced 3D fiber preform is cut according to the product design dimensions. Cutting is performed using waterjet cutting or laser cutting processes, resulting in clean, burr-free edges. The cut preform is then placed in an oven for drying at 100-120°C for 2-6 hours to remove moisture and residual sizing agent from the fiber surface. The dried preform should be immediately proceeded to the next step or stored in a sealed, dry environment to prevent moisture absorption.
[0033] Preferably, step (2) specifically includes the following steps: (2) -1. The three-dimensional fiber preform is placed in a supercritical reactor. The temperature of the supercritical reactor is controlled to rise to 35~50℃ and the pressure to rise to 8~15MPa. A supercritical fluid containing active substances with reactive functional groups is introduced for treatment for 0.5~2.0 hours to form an interface activation layer. During this process, the high diffusivity of the supercritical fluid allows the active substances with reactive functional groups to penetrate evenly into the interior of the preform and react with the silanol groups on the fiber surface to introduce active functional groups (-NH2, -OH, -SH, -epoxy groups, etc.) on the fiber surface, forming an interface activation layer with a thickness of 1~5nm. (2) -2. Control the temperature of the supercritical reactor to 40~60℃ and the pressure to 10~20MPa, and introduce supercritical fluid containing the first functional precursor for 1.0~3.0 hours to form an organic-inorganic hybrid transition layer. Utilize the high solubility of the supercritical fluid for the first precursor and its high permeability to the fiber to make the first functional precursor uniformly deposited on the surface of the activation layer. Control the mass of water in the reactor to 3~8wt% of the mass of the first functional precursor. That is, by adding a trace amount of water or utilizing the residual water in the system, the organic components in the first functional precursor undergo hydrolysis, condensation and / or cross-linking reactions, forming chemical bonds with the active functional groups on the activation layer. At the same time, the nano-inorganic powder is uniformly anchored on the fiber surface to form an organic-inorganic hybrid transition layer with a thickness of 20~100nm.
[0034] (2) -3. Control the temperature of the supercritical reactor to 45~70℃ and the pressure to 12~25MPa, and introduce supercritical fluid containing the second functional precursor for 1.0~4.0 hours to form an inorganic nano-ceramic functional layer and obtain a gradient modified preform. Under these conditions, the second functional precursor undergoes hydrolysis and condensation reaction in the supercritical fluid to form a dense nano-ceramic layer with a thickness of 30~150nm on the surface of the hybrid layer.
[0035] Preferably, the supercritical fluid is supercritical CO2 or supercritical nitrogen. More preferably, it is supercritical CO2. The supercritical CO2 circulation flow rate is controlled at 2~340 ml / min throughout the process, the heating rate is 0.2~2℃ / min, and the pressurization rate is 0.1~0.4 MPa / min.
[0036] Preferably, the supercritical fluid containing an active substance with reactive functional groups, the supercritical fluid containing a first functional precursor, and the supercritical fluid containing a second functional precursor are obtained through the following steps: the active substance with reactive functional groups, the first functional precursor, and the second functional precursor are respectively mixed with an alcohol solvent to form a solution; the solution is mixed with the supercritical fluid for 10-60 minutes, so that each substance exists in the supercritical fluid in a dissolved or dispersed state.
[0037] Preferably, the mass of the active substance having reactive functional groups is 0.2 to 1.5 wt% of the mass of the supercritical fluid, the mass of the first functional precursor is 3 to 12 wt% of the mass of the supercritical fluid, and the mass of the second functional precursor is 2 to 8 wt% of the mass of the supercritical fluid.
[0038] Preferably, step (3) specifically includes the following steps: (3) -1. Place the gradient modified preform in a vacuum impregnation tank, evacuate to -0.05~-0.098MPa, maintain for 5~30 minutes, and remove the gas from the pores of the preform; then, inject the dispersion slurry containing the heat-insulating filler into the impregnation tank under vacuum and completely immerse the gradient modified preform, maintain the vacuum for 5~30 minutes; then, release the vacuum, apply a positive pressure of 0.2~0.5MPa, maintain for 5~30 minutes, so that the slurry can fully penetrate into the three-dimensional network of the gradient modified preform.
[0039] (3)-2. Repeat the vacuum-pressure cycle of step (3)-1 1 to 5 times to ensure that the filler is evenly and fully filled into all the pores of the preform, and then pre-dry.
[0040] Preferably, the dispersion slurry containing the heat-insulating filler is obtained by dispersing the heat-insulating filler in water and / or an alcohol solvent, and the solid content of the dispersion slurry is 10-25 wt%. Preferably, the alcohol solvent is one or more of ethanol and isopropanol. Preferably, a dispersant may be further added to the dispersion slurry, such as sodium dodecylbenzenesulfonate or polyvinylpyrrolidone, and the amount of dispersant added is 0.5-2.0 wt% of the total solid mass.
[0041] The method for preparing the dispersion slurry containing the heat-insulating functional filler includes: adding the heat-insulating functional filler and dispersant to water and / or an alcohol solvent, and stirring in a high-speed disperser at a speed of 1000~5000 rpm for 0.5~2.0 hours to prepare a uniformly dispersed slurry.
[0042] Further preferably, the pre-drying includes: removing the filled preform from the impregnation tank, placing it in a ventilated area to drain excess slurry, and then placing it in an oven at 60~80℃ to dry for 2~6 hours to remove most of the solvent.
[0043] Preferably, the drying in step (4) is supercritical drying, which includes: placing the pre-dried preform in a supercritical drying vessel, introducing supercritical CO2 fluid (temperature 40~50℃, pressure 10~15MPa), maintaining for 15~30min, controlling the supercritical CO2 fluid flow rate to 2~200ml / min, and removing the residual solvent and moisture to obtain a dry preform with intact structure and no shrinkage.
[0044] Preferably, the gradient molding process in step (4) includes three stages: First stage (low-temperature pre-compression): molding temperature is 10~40℃, molding pressure is 5~12T, and holding time is 2~20s; this stage initially densifies the material and removes excess gas. Second stage (medium-temperature compression): molding temperature is 42~70℃, molding pressure is 13~25T, and holding time is 2~20s; this stage further densifies the material and promotes the bonding between the filler and the fiber network. Third stage (high-temperature setting): molding temperature is 72~100℃, molding pressure is 26~50T, and holding time is 2~20s; this stage completely sets the material, eliminates internal stress, and forms the final structure.
[0045] Preferably, after molding, an explosion-proof heat insulation sheet with a thickness of 1~10 mm is obtained.
[0046] Preferably, after molding, a further encapsulation step is performed: a film is applied to the thermal insulation material, and then encapsulated after vacuum hot pressing for shaping. The film material can be one or both of polyimide (PI) and polyethylene terephthalate (PET). The hot pressing conditions include: temperature 100~150℃, pressure 0.1~0.5MPa, and time 1~5 minutes. The film thickness can be 5~50μm.
[0047] The third aspect of the present invention provides the application of the above-mentioned explosion-proof and heat-insulating material for batteries based on three-dimensional fiber preforms as a heat-insulating material in batteries.
[0048] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a battery explosion-proof and heat-insulating material based on a three-dimensional fiber preform. It uses a three-dimensional high-temperature resistant fiber network as a mechanical support skeleton, and constructs a gradient interface layer with gradually changing composition, structure and function on the fiber surface in situ, and fills it with multi-scale heat-insulating fillers. This is a brand-new material system that achieves multi-functional integrated thermal protection with lightweight, low thermal conductivity, high temperature resistance, compressibility and impact resistance.
[0049] 2. This invention innovatively employs supercritical fluid as a carrier for in-situ gradient modification. Utilizing its high diffusivity, high solubility, and high fiber permeability, it allows reactive functional groups and functional precursors to uniformly penetrate into the preform, undergoing in-situ hydrolysis, condensation, and chemical bonding reactions. This synergistic mechanism successfully constructs a dense, high-temperature resistant protective barrier, eliminates interfacial stress, and strengthens the bond between the inorganic metal oxide ceramic material and the fiber. This facilitates the uniform filling of subsequent multi-scale functional fillers and avoids problems such as easy powder shedding and loose structure.
[0050] 3. The effective combination of the three-dimensional fiber preform, gradient interface layer, and thermal insulation filler of this invention achieves multi-scale and wide-temperature-range performance synergy. This unique explosion-proof and thermal insulation material solves the contradiction between "high compressibility" and "low thermal conductivity / high temperature resistance" in the prior art. In actual application tests, it exhibits low thermal conductivity at both room temperature and high temperature, and demonstrates excellent impact resistance (no cracking or puncture) during thermal runaway. It significantly extends the duration of thermal propagation suppression and greatly improves the safety protection capability for equipment such as battery packs.
[0051] 4. In the preparation process of this invention, a vacuum-pressure cycling process is preferably used for slurry impregnation to ensure that the filler is uniformly and fully filled into all pores of the three-dimensional network. Simultaneously, a three-stage gradient molding process, including low-temperature pre-pressing, medium-temperature pressurization, and high-temperature setting, is employed in the molding stage. Further control of these preferred preparation parameters is beneficial for producing lightweight explosion-proof heat insulation sheets with superior compressive strain and better thermal insulation performance.
[0052] 5. The explosion-proof and heat-insulating material and its preparation method provided by this invention have widely available raw materials, stable and controllable processes, and mature and reliable equipment, making them suitable for large-scale industrial production. The prepared material has excellent comprehensive performance and can be widely used in thermal runaway protection in fields such as new energy vehicle lithium batteries, energy storage power stations, and consumer electronics, resulting in significant economic and social benefits. Attached Figure Description
[0053] Figure 1 This is a process flow diagram of the preparation method of the present invention.
[0054] Figure 2 This is a schematic diagram of the supercritical fluid in-situ gradient modification device used in this invention.
[0055] Figure 3 These are SEM images of the three-dimensional fiber preform in Embodiment 1 of the present invention at different modification stages.
[0056] Figure 4 This is a comparison chart of the temperature resistance performance of the thermal insulation material after gradient modification in Example 1 of the present invention and the unmodified thermal insulation material in Comparative Example 1 (butane flame ablation test at 1200℃).
[0057] Figure 5 This is a comparison chart of the compression strain curves of the thermal insulation materials prepared in Example 1 and Comparative Example 2 of the present invention.
[0058] Figure 6 The image shows the explosion-proof heat insulation sheet prepared in Example 1 of this invention after a thermal runaway test of the battery cell, indicating that the material has no cracks or perforations.
[0059] Figure 7 This is a thermal runaway temperature rise curve of the battery cell in Embodiment 1 of the present invention. Detailed Implementation
[0060] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.
[0061] In some embodiments of the present invention, the preparation process of the explosion-proof and heat-insulating material is as follows: Figure 1 As shown, the specific steps include: (1) Preparation of three-dimensional fiber preforms (1) -1. Fiber opening treatment: The high-temperature resistant fiber raw material is fed into an opening machine with a double-pinning roller structure for opening treatment. The speed of the first pinning roller is 600~1000rpm, and the speed of the second pinning roller is 800~1200rpm. The pinning roller needle cloth is a self-locking metal needle cloth with a needle height of 3~5mm. The opening treatment time is 2~5 minutes. The opened fiber is fluffy, and the bulk density is reduced to 1 / 5~1 / 10 of the original fiber. The breaking strength retention rate of the opened fiber is ≥90%. (1)-2. Fiber web formation: The opened fibers are processed into a fiber web using an air-jet web forming machine or a carding web forming machine. Short fibers with a length of 6~15mm are formed using air-jet web forming, and the process includes: using an air-jet web forming machine with an airflow controlled at 1500~3000m³ / h. 3 The belt speed is controlled at 1~5 m / min. During the web forming process, a suction device is installed below the forming belt to remove excess airflow, while simultaneously allowing the fibers to adhere more tightly to the belt. The surface density of the formed fiber web is 30~100 g / m². 2 The thickness uniformity deviation is ≤5%. Fibers with a length of 15~30mm are processed into a web using a carding process, including: using a roller carding machine with a main cylinder speed of 400~800rpm, a work roller speed of 80~150rpm, and a take-up roller speed of 200~400rpm. The resulting fiber web surface density is 40~120g / m². 2 .
[0062] (1)-3. Multilayer lamination: The fiber web prepared above is laminated in multiple layers according to the designed thickness and areal density. The number of layers is calculated based on the target thickness of the preform, usually 6 to 20 layers. Cross-laying can be used during lamination, that is, the laying directions of adjacent fiber webs alternate between 0° and 90° (the overall layup sequence is 0° / 90° / 0° / 90° / …) to enhance the isotropy of the preform.
[0063] (1)-4. Reinforcement: Needle Punching Reinforcement: After lamination, the fiber web is fed into a needle punching machine for needle punching reinforcement. The needle punching machine adopts a double-needle plate structure, with a needle punching frequency of 200~500 needle punches / min, a needle punching depth of 6~12mm, and a needle punching density of 80~200 needle punches / cm². 2 .
[0064] Alternatively, layered stitching: After layering the fiber cloth in the design direction, sew it together with a sewing machine. The sewing thread is the same material as the fiber cloth, and the stitching interval is 5~15mm to form a layered stitched prefabricated body.
[0065] (1)-5. Cutting and Drying: The needle-punched and reinforced three-dimensional fiber preform is cut according to the product design dimensions. Water jet cutting or laser cutting is used for cutting, resulting in neat edges without burrs. The cut preform is placed in an oven for drying at a temperature of 100~120℃ for 2~6 hours.
[0066] (2) Preparation of gradient modified preforms A schematic diagram of the supercritical fluid in-situ gradient modification device used in this invention is shown below. Figure 2 As shown, it includes a supply unit, a reaction unit, and a separation and circulation unit. The supply unit includes a supercritical CO2 gas source, a high-pressure pump, a precursor dissolution tank, and a mixer. The reaction unit includes a reaction vessel, a temperature controller, and a pressure controller. The separation and circulation unit includes a separation vessel and a circulation pump. Supercritical fluids containing reactive functional groups, supercritical fluids containing a first functional precursor, and supercritical fluids containing a second functional precursor are prepared in the supply unit as follows: the reactive functional group, the first functional precursor, and the second functional precursor are respectively mixed with an alcohol solvent in the precursor dissolution tank to form a solution; the solution is then mixed with the supercritical fluid in the mixer for 10–60 min, so that each substance exists in a dissolved or dispersed state in the supercritical fluid. The three-dimensional fiber preform is placed in a reactor (the reactor is controlled by temperature and pressure), and supercritical fluid containing an active substance with reactive functional groups, supercritical fluid containing a first functional precursor, and supercritical fluid containing a second functional precursor are sequentially introduced. An interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nano-ceramic functional layer are constructed in situ on the fiber surface inside the preform, resulting in a gradient-modified preform. The entire process involves supercritical CO2 circulation flow rate controlled at 2~340 ml / min, a heating rate of 0.2~2℃ / min, and a pressure increase rate of 0.1~0.4 MPa / min. The specific steps include the following: (2) -1. Raise the temperature of the supercritical reactor containing the three-dimensional fiber preform to 35~50℃ and the pressure to 8~15MPa. Introduce a supercritical fluid containing reactive functional groups (the mass of the reactive functional groups is 0.2~1.5wt% of the mass of the supercritical fluid) into the reactor and treat for 0.5~2.0 hours. Form an interface activation layer with a thickness of 1~5nm.
[0067] (2) -2. Adjust the temperature of the supercritical reactor to 40~60℃ and the pressure to 10~20MPa. Introduce a supercritical fluid containing the first functional precursor (the mass of the first functional precursor is 3~12wt% of the mass of the supercritical fluid) into the reactor. Control the mass of water to 3~8wt% of the mass of the first functional precursor. Treat for 1.0~3.0 hours to form an organic-inorganic hybrid transition layer with a thickness of 20~100nm.
[0068] (2) -3. Adjust the temperature of the supercritical reactor to 45~70℃ and the pressure to 12~25MPa. Introduce a supercritical fluid containing a second functional precursor (the mass of the second functional precursor is 2~8wt% of the mass of the supercritical fluid) into the reactor and treat for 1.0~4.0 hours to form a dense nano-ceramic layer with a thickness of 30~150nm.
[0069] (3) Multi-scale functional filler filling A vacuum-pressure cycling process is used to fill the network pores of the gradient-modified preform with a dispersion slurry containing thermally insulating fillers; the specific operation is as follows: (3)-1. Preparation of filler slurry: Add aerogel heat insulation powder, infrared radiation material and inorganic toughening material to water and / or alcohol solvent according to a predetermined mass ratio, and add dispersant accounting for 0.5~2.0wt% of the total solid mass. Stir in a high-speed disperser at a speed of 3000~5000rpm for 0.5~2.0 hours to prepare a uniformly dispersed slurry with a solid content of 10~25wt%.
[0070] (3) -2. Vacuum impregnation: Place the modified preform in a vacuum impregnation tank, evacuate to -0.05~-0.098MPa, and maintain for 5~30 minutes; then, inject the filler slurry into the impregnation tank under vacuum to completely immerse the preform, and maintain the vacuum for 5~30 minutes. Subsequently, release the vacuum, apply a positive pressure of 0.2~0.5MPa, and maintain for 5~30 minutes to allow the slurry to fully penetrate into the three-dimensional network of the preform.
[0071] (3) -3. Cyclic impregnation: Repeat the above vacuum-pressure cycle 1 to 5 times to ensure that the filler is evenly and fully filled into all the pores of the preform. After filling, take the preform out of the impregnation tank, place it in a ventilated place to drain excess slurry, and then put it in an oven at 60 to 80°C for pre-drying for 2 to 6 hours to remove most of the solvent.
[0072] (4) Drying, gradient molding and packaging (4) -1. Supercritical drying: Place the pre-dried preform in a supercritical drying kettle, introduce supercritical CO2 (temperature 40~50℃, pressure 10~15MPa), and maintain for 12~48 hours to remove the residual solvent and moisture, and obtain a dry preform with complete structure and no shrinkage.
[0073] (4)-2. Gradient molding: The dried blank is placed in a molding die and the final molding is carried out using a gradient molding process. The gradient molding process includes three stages: Stage 1: Molding temperature is 10~40℃, molding pressure is 5~12T, and holding time is 2~20s. Stage 2: Molding temperature is 42~70℃, molding pressure is 13~25T, and holding time is 2~20s. Stage 3: Molding temperature is 72~100℃, molding pressure is 26~50T, and holding time is 2~20s.
[0074] (4) -3. Encapsulation: Cover the surface of the molded explosion-proof heat insulation sheet with a PI film or PET film (thickness of 5~50μm), and perform hot pressing encapsulation under vacuum conditions (temperature 100~150℃, pressure 0.1~0.5MPa, time 1~5 minutes) to obtain the final explosion-proof heat insulation material product.
[0075] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0076] High-silica fiber: purchased from Linyi Haoquan Silicon Industry Technology Co., Ltd., with SiO2 content ≥96%, fiber diameter 9±1μm, and length 6mm.
[0077] Alumina fiber: 10μm in diameter and 8mm in length.
[0078] Nano-zirconium silicate: D50=50nm, purchased from Zibo Yishun Ceramic Glaze Co., Ltd.
[0079] Zirconium n-propoxide: purchased from Sigma-Aldrich.
[0080] Silica aerogel: D50=50nm, purchased from Shenzhen Zhongning Technology Co., Ltd.
[0081] Silicon carbide: D50=5μm, purchased from Shandong Jinmeng New Material Co., Ltd.
[0082] Potassium hexatite whiskers: aspect ratio 20, diameter 2μm, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0083] Silicon carbide whiskers: aspect ratio 20, diameter 1μm.
[0084] Example 1
[0085] The specific steps of the preparation method of the explosion-proof and heat-insulating material based on the three-dimensional fiber preform in this embodiment are as follows: (1) Preparation of three-dimensional fiber preforms (1) -1. Fiber opening treatment: High-silica fibers are fed into a double-roller opening machine. The speed of the first roller is 800 rpm, and the speed of the second roller is 1000 rpm. The needle cloth of the rollers is a self-locking metal needle cloth with a needle height of 4 mm. The opening treatment time is 3 minutes. The opened fibers are fluffy, and the bulk density is reduced to about 1 / 8 of the original fibers. There is no obvious agglomeration between fibers, and the measured breaking strength retention rate is 94%.
[0086] (1)-2. Fiber web formation: The opened fibers are fed into an airflow web forming machine (model: LW-1800), and the airflow is controlled at 2200 m³ / h. 3 The belt speed is controlled at 3 m / min. Fibers are blown onto the forming belt by a high-speed airflow. A suction device is installed below the forming belt to remove excess airflow, simultaneously allowing the fibers to adhere more tightly to the belt. The resulting fiber web surface density is 60 g / m². 2 The thickness uniformity deviation is ±3%, and the fibers are randomly distributed in three dimensions with good isotropy.
[0087] (1)-3. Multi-layer stacking and needle reinforcement: based on the target precast body thickness of 4.0 mm and density of 0.25 g / cm³. 3 The calculated number of layers is 12. A cross-laying method is used during lamination, meaning the laying directions of adjacent fiber mesh layers alternate between 0° and 90° to enhance the isotropy of the preform. After lamination, the fiber mesh layers are fed into a needle-punching machine (model: NZ-2000) for needle-punching reinforcement. The needle-punching machine uses a double-needle plate structure, with a needle-punching frequency of 350 needles / min, a needle-punching depth of 8mm, and a needle-punching density of 120 needles / cm². 2 During the needle-punching process, the needle carries fiber bundles through the fiber network layers, forming fiber clusters in the thickness direction, which mechanically lock the fiber network layers together. The precast structure after needle-punching reinforcement is stable, and the measured peel strength in the thickness direction is 0.7 N / cm.
[0088] (1)-4. Cutting and Drying: The needle-punched and reinforced three-dimensional fiber felt preforms are cut into 200 mm × 200 mm squares according to the product design dimensions. Water jet cutting is used for cutting, resulting in neat edges without burrs. The cut preforms are then placed in an oven for drying at 105℃ for 4 hours to remove moisture and residual sizing agent from the fiber surface. The dried preforms are immediately proceeded to the next step.
[0089] (2) In-situ gradient modification of supercritical fluid (2)-1. Place the three-dimensional fiber felt preform prepared in step (1)-4 in a supercritical reactor, raise the temperature to 40℃, and raise the pressure to 12MPa. Dissolve the silane coupling agent KH-560 in anhydrous ethanol at a concentration of 0.5wt%. Mix the KH-560 solution with supercritical CO2 in a mixer using a high-pressure pump, so that the mass percentage of KH-560 in supercritical CO2 is 0.3wt%. Pass the mixed fluid into the reactor and treat for 1.5 hours. During this process, supercritical CO2 carries KH-560 into the interior of the preform, reacts with the silanol groups on the fiber surface, introduces amino groups on the fiber surface, and forms an interfacial activation layer with a thickness of about 3nm. After treatment, separate the ethanol and unreacted KH-560 in the fluid through a separation vessel, and recover the supercritical CO2 for recycling.
[0090] (2) -2. Adjust the temperature of the reactor to 50℃ and the pressure to 15MPa. Prepare the first functional precursor solution: Mix melamine and nano-zirconium silicate at a mass ratio of 1:5, add to anhydrous ethanol, and ultrasonically disperse for 30 minutes to prepare a dispersion with a solid content of 8wt%; mix the dispersion with supercritical CO2 so that the first functional precursor accounts for 5wt% of the mass of supercritical CO2. Pass the mixed fluid into the reactor, control the mass of water to be 5wt% of the mass of the first functional precursor, and treat for 2.0 hours. Under these conditions, melamine undergoes a cross-linking reaction with the fiber surface groups, and at the same time, nano-zirconium silicate is uniformly attached to the fiber surface through chemical bonding and physical anchoring, forming an organic-inorganic hybrid transition layer with a thickness of about 60nm.
[0091] (2)-3: Adjust the reactor temperature to 55℃ and the pressure to 18MPa. Prepare the second functional precursor solution: Dissolve zirconium propoxide in anhydrous ethanol to a concentration of 5wt%; mix the solution with supercritical CO2 to make the zirconium propoxide account for 3wt% of the supercritical CO2 by mass. Pass the mixed fluid into the reactor and treat for 2.5 hours. Under these conditions, zirconium propoxide undergoes hydrolysis and condensation reaction using the trace amount of water remaining in the supercritical CO2, forming a dense ZrO2 nano-ceramic layer with a thickness of about 80nm on the surface of the hybrid layer. After treatment, slowly release the pressure to atmospheric pressure and remove the modified preform.
[0092] Figure 3 The images show SEM images of the three-dimensional fiber preform in Example 1 of this invention at different modification stages; (a) shows the original high-silica fiber with a smooth surface; (b) shows the surface with nanoscale active sites after the activation step; (c) shows the fiber surface uniformly coated with an organic-inorganic hybrid layer after the hybrid layer construction; and (d) shows the fiber surface with a dense ZrO2 nano-ceramic layer with a thickness of about 80 nm after the ceramic layer construction.
[0093] (3) Multi-scale functional filler filling (3)-1. Preparation of filler slurry: Weigh 60 parts of silica aerogel, 25 parts of silicon carbide, and 15 parts of potassium hexatitanate whiskers according to the mass ratio, for a total of 100 parts. Add the above solid powder to 200 parts of anhydrous ethanol, add sodium dodecylbenzenesulfonate dispersant accounting for 1.0 wt% of the total solid mass, and stir in a high-speed disperser at a speed of 4000 rpm for 1.0 hour to prepare a uniformly dispersed slurry with a solid content of about 15 wt%.
[0094] (3)-2. Vacuum impregnation: Place the modified preform from step S2 into a vacuum impregnation tank, evacuate to -0.098 MPa, and maintain for 15 minutes. Inject the prepared filler slurry into the impregnation tank under vacuum to completely immerse the preform, and maintain the vacuum for 20 minutes. Then release the vacuum, apply a compressed air pressure of 0.3 MPa, and maintain for 20 minutes.
[0095] (3)-3. Cyclic impregnation: Repeat step (3)-2 above 3 times to ensure that the filler is evenly and fully filled into all pores of the preform. Take out the preform after filling and place it in a fume hood to drain excess slurry; place the preform after filling in a 70°C oven to dry for 4 hours to remove most of the ethanol.
[0096] (4) Drying and gradient molding (4) -1. Supercritical drying: The pre-dried preform is placed in a supercritical drying kettle, and supercritical CO2 (temperature 45℃, pressure 12MPa) is introduced and kept for 24 hours to remove the residual solvent and moisture, and obtain a dry preform with complete structure and no shrinkage.
[0097] (4)-2. Gradient molding: The dried blank is placed in a molding die and a gradient molding process is adopted: First stage: molding temperature 30℃, molding pressure 10T, holding time 10s; Second stage: molding temperature 50℃, molding pressure 20T, holding time 10s; Third stage: molding temperature 80℃, molding pressure 30T, holding time 15s. After molding, an explosion-proof heat insulation sheet with a thickness of 3.3mm is obtained.
[0098] (4)-3. Encapsulation: A 25μm thick polyimide (PI) film is applied to the upper and lower surfaces of the heat insulation sheet. The film is then heat-pressed in a vacuum hot press (temperature 120℃, pressure 0.2MPa, time 3 minutes) to obtain the final explosion-proof heat insulation material product.
[0099] Example 2
[0100] The difference between Example 2 and Example 1 is only that steps (2)-3 in Example 2 are: adjusting the reactor temperature to 50°C and the pressure to 16 MPa. The second functional precursor solution is prepared by dissolving aluminum sec-butoxide in anhydrous ethanol at a concentration of 5 wt%; the solution is then mixed with supercritical CO2, ensuring that aluminum sec-butoxide accounts for 5 wt% of the supercritical CO2. The mixed fluid is then introduced into the reactor and treated for 3.0 hours. Under these conditions, aluminum sec-butoxide undergoes hydrolysis and condensation, forming a dense Al2O3 nanoceramic layer with a thickness of approximately 70 nm on the surface of the hybrid layer.
[0101] The remaining steps are the same as in Example 1.
[0102] Example 3
[0103] The only difference between Example 3 and Example 1 is that step (1) of the preparation of the three-dimensional fiber preform in Example 3 includes the following steps: (1) -1. Fiber opening treatment: Alumina fibers are fed into a double-pinning roller opening machine. The speed of the first pinning roller is 800 rpm, and the speed of the second pinning roller is 1000 rpm. The pinning roller needle cloth is a self-locking metal needle cloth with a needle height of 4 mm. The opening treatment time is 3 minutes. The opened fibers are fluffy, and the bulk density is reduced to about 1 / 8 of the original fibers. There is no obvious agglomeration between fibers, and the measured breaking strength retention rate is 95%.
[0104] (1)-2. A three-dimensional four-way weaving process is used to weave alumina fibers into a three-dimensional woven preform with a weaving angle of 30°, a fiber volume fraction of 28%, and a preform thickness of 4mm. The weaving equipment is a three-dimensional weaving machine with a weaving speed of 0.5 m / min.
[0105] (1)-3 Cutting and drying treatment: Same as (1)-4 in Example 1.
[0106] The remaining steps are the same as in Example 1.
[0107] Example 4
[0108] The difference between Example 4 and Example 1 is that in step (3)-1 of Example 4, 15 parts of silicon carbide whiskers are used to replace potassium hexatitanate whiskers, while other components and proportions remain unchanged.
[0109] The remaining steps are the same as in Example 1.
[0110] Example 5
[0111] The difference between Example 5 and Example 1 is that the processing times in steps (2)-1, (2)-2, and (2)-3 of Example 5 are 0.5 hours, 1.0 hours, and 1.5 hours, respectively. By shortening the processing time, the thickness of each layer is reduced accordingly (the activation layer is about 1 nm, the hybrid layer is about 30 nm, and the ceramic layer is about 40 nm).
[0112] The remaining steps are the same as in Example 1.
[0113] Example 6
[0114] The difference between Example 6 and Example 1 is that step (4)-2 of gradient molding in Example 6 is specifically as follows: First stage: molding temperature 25℃, molding pressure 8T, holding time 5s; Second stage: molding temperature 45℃, molding pressure 15T, holding time 5s; Third stage: molding temperature 70℃, molding pressure 25T, holding time 10 s.
[0115] The remaining steps are the same as in Example 1.
[0116] Example 7
[0117] The difference between Example 7 and Example 1 is that step (4)-2 of Example 7 is specifically: molding temperature 80℃, molding pressure 30T, and holding time 20s.
[0118] The remaining steps are the same as in Example 1.
[0119] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not perform the supercritical fluid in-situ gradient modification in step (2), that is, the three-dimensional fiber felt preform prepared in step (1) is directly filled in step (3) and dried, gradient molded and packaged in step (4).
[0120] Comparative Example 2 This comparative example uses the apparatus and process disclosed in CN2025105500204 to pretreat discrete fibers, then re-prepares the preform and performs subsequent filling and molding. The pretreatment is as follows: S1 Using the disperser described in CN2025105500204, high-silica fibers (same as in Example 1) are fed into the inner liner, and high-speed gas at 100°C and 25 m / s is introduced for 10 min to obtain surface-roughened fibers. S2 Melamine solution is introduced in atomized form and treated for 8 min to form a surface treatment agent layer on the fiber surface. S3 Nano-zirconia (D50=50nm) is introduced into the inner liner and treated for 20 min, and the nano-powder is coated on the fiber surface by high-speed gas impact. S4 The treated fibers are removed. Then, the three-dimensional fiber felt preform (needle-punching process, density 0.25 g / cm³) is re-prepared according to the method of step (1) in Example 1. 3 (4mm thick). Then, follow step (3) of Example 1 to fill the filler, and then follow step (4) of Example 1 to dry, mold, and encapsulate.
[0121] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, step (2) is performed only in (2)-1 and (2)-2, without the construction of the nano-ceramic layer in (2)-3. The other steps are the same as in Example 1. That is, the modified fiber surface only has an activation layer and a hybrid transition layer, without an outer ZrO2 ceramic layer.
[0122] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, step (2) is performed only in (2)-1 and (2)-3, without constructing the hybrid transition layer in (2)-2. The other steps are the same as in Example 1. That is, the modified fiber surface only has an activation layer and a ZrO2 ceramic layer, without the intermediate hybrid transition layer.
[0123] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that in step (2)-2 of Comparative Example 5, the first functional precursor is melamine, and the rest is the same as in Example 1.
[0124] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is that in step (2)-2 of Comparative Example 6, the first functional precursor is nano-zirconium silicate, and the rest is the same as in Example 1.
[0125] Comparative Example 7 The only difference between Comparative Example 7 and Example 1 is that in step (2)-2 of Comparative Example 7, the mass of water is controlled to be 1 wt% of the mass of the first functional precursor, and the rest is the same as in Example 1.
[0126] Comparative Example 8 The only difference between Comparative Example 8 and Example 1 is that in step (2)-2 of Comparative Example 8, the mass of water is controlled to be 10 wt% of the mass of the first functional precursor, and the rest is the same as in Example 1.
[0127] The following performance tests were performed on the thermal insulation materials prepared in Examples 1-7 and Comparative Examples 1-8: 1. Thermal conductivity test Thermal conductivity at 25℃: Tested according to GB / T10295-2008 using the heat flow meter method.
[0128] Thermal conductivity at 800℃: Tested according to YB / T4130-2005.
[0129] 2. Thermal insulation performance test A butane flame torch (flame temperature 1200±50℃) was used to ablate the center of the front side of the heat insulation sheet for 20 minutes. The temperature change on the back side (cold side) was recorded using a thermocouple, and the highest temperature after stabilization was recorded.
[0130] 3. Compression strain test The test was conducted according to GB / T13480-2014. The samples were cut into 50mm×50mm cubes and compressed using a computer-controlled electronic universal testing machine at a compression rate of 0.02mm / s. The compression strain was recorded at pressures of 1.0MPa and 2.0MPa.
[0131] 4. Heat spread suppression time and impact resistance test Four 73Ah soft-pack ternary lithium battery cells and thermal insulation sheets were arranged in the manner of "cell-thermal insulation sheet-cell-thermal conductive sheet-cell-thermal insulation sheet-cell". One of the cells was heated until thermal runaway was triggered. The temperature rise curves of adjacent cells and the time of thermal runaway were recorded. The thermal propagation suppression time (the time interval between the thermal runaway of the first cell and the thermal runaway of the second cell) was calculated. The thermal insulation sheet was observed to see if it cracked.
[0132] Table 1. Performance test results of the examples and comparative examples.
[0133] Results analysis: (1) The advancement of the process route: Based on the data in Table 1 and Figure 5Comparing Example 1 and Comparative Example 2, although both constructed fiber surface modification layers, the overall performance of Example 1 (supercritical in-situ modification) is significantly better than that of Comparative Example 2 (pre-treated discrete fibers using process CN2025105500204). The thermal conductivity of Example 1 at 25℃ (0.0172 W / (m·K)) and at 800℃ (0.0265 W / (m·K)) is lower than that of Comparative Example 2 (0.0225 and 0.0380), indicating better thermal insulation (162℃ vs 210℃) and a longer heat spread suppression time (1310 s). Figure 7 (vs 450s). This demonstrates that the process route of the present invention, which involves "prefabrication followed by in-situ modification", can better maintain the integrity of the three-dimensional network and achieve a more uniform and robust gradient interface layer.
[0134] (2) Necessity of gradient interface structure: Comparing Example 1 and Comparative Example 3, Comparative Example 3 only constructed a hybrid layer and did not form an inorganic ceramic layer. Its thermal conductivity at 800℃ (0.0360) and thermal insulation performance at 195℃ were inferior to those of Example 1 (0.0265, 162℃). This proves that the outermost inorganic nano-ceramic layer (ZrO2) is crucial for improving high-temperature thermal insulation and temperature resistance. Comparing Example 1 and Comparative Examples 4-6, Comparative Example 4 did not construct an organic-inorganic hybrid transition layer, Comparative Example 5's transition layer contained only organic components, and Comparative Example 6's transition layer contained only inorganic powder components. The thermal conductivity and insulation performance of Comparative Examples 4-6 were lower than those of Example 1, and their heat spread suppression time was significantly lower than that of Example 1. The insulation performance of Comparative Examples 5 and 6, whose transition layers consisted only of organic or inorganic components, was actually lower than that of Comparative Example 4, which had no transition layer. This is because the addition of melamine alone in Comparative Example 5 had a counterproductive effect, leading to poor coating in the next step and ultimately poor performance. The hybrid transition layer of Comparative Example 6 did not contain melamine, essentially mixing in an inorganic powder, which did not coat the fibers and also affected the coating in the next step, causing the material to burn through quickly. This demonstrates that a hybrid transition layer constructed from organic and inorganic components is more beneficial for improving the performance of the insulation sheet. (Comparative Example 1 and Comparative Example 1 (compare the data in Table 1 and...)) Figure 4 The unmodified preform (Comparative Example 1) performed the worst, demonstrating the necessity of gradient interface modification.
[0135] (3) Necessity of controlling water quality: The first functional precursor of this application is composed of organic components and nano-inorganic powders, in which the organic components participate in the hydrolysis reaction. The system needs to provide a moderate excess of water to ensure sufficient reaction. When the water content of the system is low (such as in Comparative Example 7 where the mass of water is 1% of the mass of the first functional precursor), the degree of hydrolysis reaction is seriously insufficient, and the effective hydrolysis and condensation of the organic components cannot be guaranteed. When the water content of the system is high (such as when the mass of water is 10% of the mass of the first functional precursor), the precursor may gel prematurely in supercritical CO2, forming uneven large particle aggregates. The moisture content directly affects the final performance of the thermal insulation material, especially causing a significant decrease in thermal insulation performance.
[0136] (4) Influence of process parameters: Comparing Examples 1 and 5, it can be seen that shortening the processing time of each step (Example 5) reduces the thickness of each interface layer, resulting in a slight decrease in temperature resistance and thermal insulation performance (the cold surface temperature increases to 180°C), but it is still within an acceptable range. Comparing Examples 1 and 7, it can be seen that Example 7 uses a one-stage molding process, which results in a slight decrease in performance, indicating that the three-stage molding process of the present invention can give the thermal insulation sheet better performance. Comparing Examples 1 and 6, it can be seen that reducing the molding pressure (Example 6) slightly reduces the compressive strain. This indicates that the process parameters of the present invention can be adjusted within a certain range to meet different performance requirements.
[0137] (5) Comprehensive performance advantages: Under the premise that the thermal conductivity (0.0172 W / (m·K)) at 25℃ meets the index, Example 1 achieves excellent compressive strain (42.5%@1.0MPa, 57.2%@2.0MPa) and ultra-long heat spread suppression time (1310s), and the thermal conductivity at 800℃ remains below 0.03. This fully demonstrates that the present invention has successfully solved the fundamental contradiction between "high compression" and "low thermal conductivity / high temperature resistance" in the prior art through the completely innovative technical route of "three-dimensional prefabrication + supercritical in-situ gradient modification + multi-scale filling".
[0138] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0139] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0140] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A battery explosion-proof and heat-insulating material based on a three-dimensional fiber preform, characterized in that, include: A three-dimensional fiber preform, a gradient interface layer formed in situ on the fiber surface of the three-dimensional fiber preform, and a thermal insulation filler dispersed in the fiber network of the three-dimensional fiber preform; The gradient interface layer comprises, from the inside out: an interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nano-ceramic functional layer; The interface activation layer is formed by supercritical fluid carrying an active substance with reactive functional groups to react on the fiber surface. The active substance with reactive functional groups is a silane coupling agent, which is one or more of aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, and methacrylate-type silane coupling agents. The organic-inorganic hybrid transition layer is formed by supercritical fluid carrying a first functional precursor, which is deposited and / or reacted on the surface of the interface activation layer. The first functional precursor includes organic components and nano-inorganic powder. When forming the organic-inorganic hybrid transition layer, the mass of water in the reactor is controlled to be 3-8 wt% of the mass of the first functional precursor. The inorganic nanoceramic functional layer is formed by supercritical fluid carrying a second functional precursor, which is deposited and reacted on the surface of an organic-inorganic hybrid transition layer. After reaction, the second functional precursor forms an inorganic metal oxide ceramic material. The inorganic metal oxide ceramic material is one or more of ZrO2, Al2O3, and TiO2. The second functional precursor is a precursor substance for forming the inorganic metal oxide ceramic material, which is a metal alkoxide selected from one or more of zirconium n-propoxide, zirconium n-butoxide, aluminum isopropoxide, aluminum sec-butoxide, tetrabutyl titanate, tetraisopropyl titanate, and titanium isopropoxide. The organic component is one or more of silane coupling agents, melamine, and polysaccharides; The nano-inorganic powder is one or more of nano-zirconium silicate, nano-zirconium oxide, nano-alumina, nano-titanium dioxide, and nano-silica, and its D50 particle size is 1~200 nm. The heat-insulating filler includes aerogel heat-insulating powder, infrared radiation materials, and inorganic toughening materials.
2. The explosion-proof and heat-insulating material according to claim 1, characterized in that, The three-dimensional fiber preform is made from high-temperature resistant fibers, which are selected from one or more of the following: high-silica fibers with SiO2 content ≥96%, alumina fibers, zirconium oxide fibers, silicon carbide fibers, mullite fibers, aluminum silicate fibers, potassium hexatitanate fibers, silicon nitride fibers, hexagonal boron nitride fibers, carbon fibers, basalt fibers, and boron fibers. The bulk density of the three-dimensional fiber preform is 0.10~0.50 g / cm³. 3 The thickness is 1.0~10.0mm.
3. The explosion-proof and heat-insulating material according to claim 1, characterized in that, The supercritical fluid is one or both of supercritical CO2 fluid and supercritical nitrogen fluid.
4. The explosion-proof and heat-insulating material according to claim 1, characterized in that, The mass ratio of organic components to nano-inorganic powder is 1:2 to 1:10; And / or, the thickness of the interface activation layer is 1~5nm; And / or, the thickness of the organic-inorganic hybrid transition layer is 20~100 nm; And / or, the thickness of the inorganic nanoceramic functional layer is 30~150nm.
5. The explosion-proof and heat-insulating material according to claim 1, characterized in that, The aerogel insulating powder, infrared radiation material, and inorganic toughening material account for 40-70 wt%, 15-35 wt%, and 5-20 wt% of the total mass of the insulating functional filler, respectively. The aerogel insulation powder is selected from one or more of silica aerogel, alumina aerogel, titanium dioxide aerogel, zirconium dioxide aerogel, and titanium dioxide-silica composite aerogel, and its D50 particle size is 1~200 nm. The infrared radiation material is selected from one or more of silicon carbide, zirconium oxide, heat-reflective titanium dioxide, potassium hexatitanate whiskers, manganese dioxide, cobalt tetroxide, graphene, carbon nanotubes, titanium carbide, and aluminum nitride, and its D50 particle size is 2~50μm. The inorganic toughening material is an inorganic whisker, selected from one or more of potassium hexatitanate whiskers, silicon carbide whiskers, aluminum borate whiskers, zinc oxide whiskers, magnesium oxide whiskers, mullite whiskers, aluminum oxide whiskers, silicon nitride whiskers, calcium sulfate whiskers, calcium carbonate whiskers, and calcium magnesium silicate whiskers; the aspect ratio of the inorganic whisker is 10~30, and the diameter is 0.1~5μm.
6. A method for preparing a battery explosion-proof and heat-insulating material based on a three-dimensional fiber preform as described in claim 1, characterized in that, Includes the following steps: (1) Preparation of three-dimensional fiber preforms; (2) The three-dimensional fiber preform is placed in a supercritical reactor, and supercritical fluid containing an active substance with reactive functional groups, supercritical fluid containing a first functional precursor, and supercritical fluid containing a second functional precursor are sequentially introduced to construct an interface activation layer, an organic-inorganic hybrid transition layer, and an inorganic nano-ceramic functional layer on the fiber surface inside the preform to obtain a gradient modified preform. (3) A vacuum-pressure cycling process is used to fill the network pores of the gradient modified preform with a dispersion slurry containing heat-insulating filler. (4) The preform after filling is dried and then molded using a gradient molding process to obtain explosion-proof heat insulation material.
7. The preparation method according to claim 6, characterized in that, Step (2) includes the following steps: (2) -1. Place the three-dimensional fiber preform in a supercritical reactor, control the temperature of the supercritical reactor to rise to 35~50℃ and the pressure to rise to 8~15MPa, and introduce supercritical fluid containing active substances with reactive functional groups for 0.5~2.0 hours to form an interface activation layer; (2)-2. Control the temperature of the supercritical reactor to 40~60℃ and the pressure to 10~20MPa, and introduce supercritical fluid containing the first functional precursor for 1.0~3.0 hours to form an organic-inorganic hybrid transition layer; in step (2)-2, control the mass of water in the reactor to be 3~8wt% of the mass of the first functional precursor; (2) -3. Control the temperature of the supercritical reactor to 45~70℃ and the pressure to 12~25MPa, and introduce supercritical fluid containing the second functional precursor for 1.0~4.0 hours to form an inorganic nano-ceramic functional layer and obtain a gradient modified preform. And / or, step (3) includes the following steps: (3) -1. Place the gradient modified preform in a vacuum impregnation tank, evacuate to -0.05~-0.098MPa, and maintain for 5~30 minutes; then, inject the dispersion slurry containing heat-insulating filler into the impregnation tank under vacuum and immerse the gradient modified preform, and maintain the vacuum for 5~30 minutes; subsequently, release the vacuum, apply a positive pressure of 0.2~0.5MPa, and maintain for 5~30 minutes to allow the slurry to penetrate into the three-dimensional network of the gradient modified preform; (3)-2. Repeat the vacuum-pressure cycle of step (3)-1 1 to 5 times; And / or, the gradient molding in step (4) includes three stages: First stage: molding temperature is 10~40℃, molding pressure is 5~12T, and holding time is 2~20s; Second stage: molding temperature is 42~70℃, molding pressure is 13~25T, and holding time is 2~20s; The third stage: the molding temperature is 72~100℃, the molding pressure is 26~50T, and the holding time is 2~20s; And / or, after molding, an explosion-proof and heat-insulating material with a thickness of 1~10 mm is obtained.
8. The preparation method according to claim 6, characterized in that, Supercritical fluids containing reactive functional groups, supercritical fluids containing a first functional precursor, and supercritical fluids containing a second functional precursor are obtained through the following steps: the reactive functional group, the first functional precursor, and the second functional precursor are respectively mixed with an alcohol solvent to form a solution; the solution is mixed with the supercritical fluid for 10-60 min, so that each substance exists in the supercritical fluid in a dissolved or dispersed state; The active substance with reactive functional groups has a mass of 0.2 to 1.5 wt% of the supercritical fluid, the first functional precursor has a mass of 3 to 12 wt% of the supercritical fluid, and the second functional precursor has a mass of 2 to 8 wt% of the supercritical fluid.
9. The preparation method according to claim 6, characterized in that, After molding, a packaging step is performed: a film is applied to the explosion-proof and heat-insulating material, and then it is sealed after vacuum hot pressing; the hot pressing conditions include: temperature 100~150℃, pressure 0.1~0.5MPa, and time 1~5 minutes.
10. The application of the explosion-proof and heat-insulating material for batteries based on three-dimensional fiber preforms as described in claim 1 as a heat-insulating material in batteries.
Citation Information
Patent Citations
Efficient heat insulation sheet and preparation method thereof
CN111825423A
Aerogel battery cell heat insulation sheet and preparation method thereof
CN115449194A
An improved process for producing silica aerogel thermal insulation product with increased efficiency
CN107849764A
Thermal response ceramic fire-resistant explosion-proof pad and preparation method thereof
CN118930220A